Hydrogen and 40Ar/39Ar isotope evidence for multiple and protracted paleofluid flow events within the long‐lived North Anatolian Keirogen (Turkey). (28th June 2015) - Boles, Austin; van der Pluijm, Ben; Mulch, Andreas; Mutlu, Halim; Uysal, I. Tonguç; Warr, Laurence N.
Abstract We present a new approach to identifying the source and age of paleofluids associated with low‐temperature deformation in the brittle crust, using hydrogen isotopic compositions (δD) and 40Ar/39Ar geochronology of authigenic illite in clay gouge‐bearing fault zones. The procedure involves grain‐size separation, polytype modeling, and isotopic analysis, creating a mixing line that is used to extrapolate to δD and age of pure authigenic and detrital material. We use this method on samples collected along the surface trace of today's North Anatolian Fault (NAF). δD values of the authigenic illite population, obtained by extrapolation, are −89 ± 3‰, −90 ± 2‰, and −97 ± 2‰ (VSMOW) for samples KSL, RES4‐1, and G1G2, respectively. These correspond to δD fluid values of −62‰ to −85‰ for the temperature range of 125°C ± 25°, indistinguishable from present‐day precipitation values. δD values of the detrital illite population are −45 ± 13‰, −60 ± 6‰, and −64 ± 6‰ for samples KSL, G1G2, and RES4‐1, respectively. Corresponding δD fluid values at 300°C are −26‰ to −45‰ and match values from adjacent metamorphic terranes. Corresponding clay gouge ages are 41.4 ± 3.4 Ma (authigenic) and 95.8 ± 7.7 Ma (detrital) for sample G2 and 24.6 ± 1.6 Ma (authigenic) and 96.5 ± 3.8 Ma (detrital) for sample RES4‐1, demonstrating a long history of meteoric fluid infiltration in the area. We conclude that today's NAF incorporated preexisting, weak clay‐rich rocks that represent earlier mineralizing fluid events. The samples preserve at least three fluid flow pulses since the Eocene and indicate that meteoric fluid has been circulating in the upper crust in the North Anatolian Keirogen since that time.